Lasers in the Conservation of Artworks XIII Proceedings of the International Conference on Lasers in the Conservation of Artworks XIII (LACONA XIII), 12-16 September 2022, Florence, Italy - Siano, Salvatore; Ciofini, Daniele (Taylor & Francis, 2024)
Light allows us not only to see the works of art, but also to take care of them and preserve them for future generations, through diagnosis of the degradation and deterioration phenomena, conservation treatments, and monitoring based on light-material interaction processes. Recent progress on this subject was discussed during the 13th International Conference on Lasers in the Conservation of Artworks (LACONA XIII, Florence, Italy, 12-16 September 2022). This volume includes selected contributions presented at the conference on preservation topics, photonic techniques, and optimization methods. In particular, the papers focus on the development and use of innovative spectroscopic and imaging characterization techniques, the diagnostic knowledge of important artworks, and the optimization of the laser solution for preserving a growing variety of cultural assets, such as stone and metal artefacts, painted surfaces, textile, feather, and plastic artefacts. Lasers in the Conservation of Artworks XIII aims at scholars and operators of the community of preservation of cultural heritage, at teachers and students of training courses on diagnostic and conservation methods, applied physics, and chemistry, as well as archaeology and art history.